Assessment of Market milk adulteration in Tiruchirapalli city of Tamil Nadu - Rajarajan, G (Indian Journal of Dairy Science, 2021)
A study was conducted to analyze the market milk samples sold in Tiruchirapalli city of Tamil Nadu for the presence of adulterants. A total of 110 milk samples, 10 from the organized brands, 50 from local vendors and 50 from tea and coffee shops were collected. The present study revealed the presence of starch in 02 milk samples (1.82%) and that to from organized brands were detected. Â Further, the presence of neutralizers, detergents and sodium chloride were found in 36 samples (32.73%), 21 milk samples (19.09%) and 33 milk samples (30%) respectively. The skimmed milk powder was detected in all the ten organized brands. The milk samples obtained from local vendors, tea and coffee shop were negative for skimmed milk powder. The study also revealed the presence of sugar in 45 milk samples (40.91%), hydrogen peroxide in 03 samples (2.73%) and pond water/nitrate in 20 milk samples (18.18%) respectively. In addition, the study revealed that none of the sample was found positive for the presence of alizarin, formalin, urea, glucose / dextrose, cellulose, maltodextrin, protein and boric acid.